PENYELESAIAN SENGKETA KONSUMEN DALAM TRANSAKSI JUAL BELI ONLINE MELALUI BADAN PENYELESAIAN SENGKETA - Fernanda Tasya, Raden Roro; Astutik, Sri; Handayati, Nur; Nasoetion, Deddi Wrdana (Journal of Indonesian Comparative of SyariÆah Law, 2024)
This study discusses legal protection for consumers in online buying and selling transactions and efforts to resolve disputes that occur due to default by business actors. In the digital era, online transactions are becoming increasingly popular because they are considered more practical and efficient. However, online shopping also has risks, such as goods that are not in accordance, late delivery, or even fraud. In Indonesia, legal protection for consumers in online transactions is regulated in Law Number 8 of 1999 concerning Consumer Protection and Law Number 1 of 2024 concerning Information and Electronic Transactions. Consumers who experience losses can file a lawsuit through the Consumer Dispute Resolution Agency (BPSK) or the court. This study uses a case study on the Shopee platform to analyze the effectiveness of BPSK in resolving consumer disputes. The results of the study show that BPSK is a more practical alternative than the courts in resolving consumer disputes. However, there are still many obstacles in its implementation, such as a lack of consumer understanding of the lawsuit filing procedure and the time-consuming and costly legal process. This study concludes that legal protection for consumers can be more effective if the government actively monitors online transactions and educates consumers about their rights. Efforts to resolve disputes through BPSK need to be improved to be more efficient and to meet consumer protection needs.